Risk stratification of adults with congenital heart disease during the COVID-19 pandemic: insights from a multinational survey among European experts. Issue 1 (21st April 2021) - Ruperti-Repilado, Francisco Javier; Tobler, Daniel; Greutmann, Matthias; Bouchardy, Judith; Ladouceur, Magalie; Dos-Subira, Laura; Gallego, Pastora; Gabriel, Harald; Bouma, Berto; Schwerzmann, Markus
Abstract : Objective: Adults with congenital heart disease (ACHD) may be at a higher risk of a fatal outcome in case of COVID-19. Current risk stratification among these patients relies on personal experience and extrapolation from patients with acquired heart disease. We aimed to provide an expert view on risk stratification while awaiting results from observational studies. Methods: This study was an initiative of the EPOCH (European Collaboration for Prospective Outcome Research in Congenital Heart disease). Among nine European countries (Austria, Belgium, Denmark, France, Germany, Italy, the Netherlands, Spain and Switzerland), 24 experts from 23 tertiary ACHD centres participated in the survey. ACHD experts were asked to identify ACHD-specific COVID-19 risk factors from a list of potential outcome predictors and to estimate the risk of adverse COVID-19 outcomes in seven commonly seen patient scenarios. Results: 82% of participants did not consider all ACHD patients at risk of COVID-19 related complications. There was a consensus on pulmonary arterial hypertension, Fontan physiology and cyanotic heart disease as risk factors for adverse outcomes. Among different ACHD scenarios, a patient with Eisenmenger syndrome was considered to be at the highest risk. There was a marked variability in risk estimation among the other potential outcome predictors and ACHD scenarios. Conclusions: Pulmonary arterial hypertension, Fontan palliation and cyanotic heart disease were widely considered as risk factors for poor outcome in COVID-19. However, there was a marked disparity in risk estimation for other clinical scenarios. We are in urgent need of outcome studies in ACHD suffering from COVID-19.